ChemInform Abstract: Fermented Baker′s Yeast: An Efficient Catalyst for the Synthesis of Pyran Derivatives in Water at Room Temperature. Issue 31 (11th July 2013) - Saha, M.; Pal, A. K.
Abstract Fermented baker′s yeast is shown to catalyze the synthesis of (IV), (VI), and (VII).